2002
DOI: 10.1074/jbc.m203828200
|View full text |Cite
|
Sign up to set email alerts
|

Small Inhibitory RNA Duplexes for Sp1 mRNA Block Basal and Estrogen-induced Gene Expression and Cell Cycle Progression in MCF-7 Breast Cancer Cells

Abstract: Sp1 is a member of the Sp and Krü ppel-like family of transcription factors that bind GC and CACCC boxes to regulate gene expression (1-3). Sp1 is widely expressed in multiple tissues (4), and targeted disruption of Sp1 in mice results in retarded development and embryo-lethality (5). Sp1 interacts with GC-rich Sp1 binding sites in multiple promoters to regulate gene expression, and there are an increasing number of studies showing that Sp1 interacts with other nuclear proteins, including promoter-bound transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
115
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 45 publications
16
115
1
Order By: Relevance
“…In this study, we have also used RNA interference and small inhibitory RNAs (siRNAs) for Sp1 (iSp1), Sp3 (iSp3), and Sp4 (iSp4) to investigate the role of individual Sp proteins in ERa/Sp-mediated transactivation in MCF-7 cells. Previous studies in cancer cell lines have demonstrated the specificity and effectiveness of iSp1, iSp3, and iSp4 in Sp protein knockdown (Abdelrahim et al 2002, Higgins et al 2006a, and results in Fig. 1A-C illustrate that transfected iSp1, iSp3, and iSp4 significantly decreased Sp1, Sp3, and Sp4 mRNA levels in whole cell extracts from MCF-7 cells.…”
Section: Role Of Sp Proteins Of Hormonal Activation Of Psp1mentioning
confidence: 61%
See 2 more Smart Citations
“…In this study, we have also used RNA interference and small inhibitory RNAs (siRNAs) for Sp1 (iSp1), Sp3 (iSp3), and Sp4 (iSp4) to investigate the role of individual Sp proteins in ERa/Sp-mediated transactivation in MCF-7 cells. Previous studies in cancer cell lines have demonstrated the specificity and effectiveness of iSp1, iSp3, and iSp4 in Sp protein knockdown (Abdelrahim et al 2002, Higgins et al 2006a, and results in Fig. 1A-C illustrate that transfected iSp1, iSp3, and iSp4 significantly decreased Sp1, Sp3, and Sp4 mRNA levels in whole cell extracts from MCF-7 cells.…”
Section: Role Of Sp Proteins Of Hormonal Activation Of Psp1mentioning
confidence: 61%
“…Cells were transfected with iNS1 (non-specific RNA), iSp1, iSp3 or iSp4 for 55-60 h, then treated with Me 2 SO or 10 nM E 2 for an additional 12 h and mRNA levels were determined in whole cell extracts by real-time PCR. Previous studies show that within this time period, there is a maximal decrease of Sp proteins using these siRNAs (Abdelrahim et al 2002, Higgins et al 2006a. Basal E 2 F1 mRNA levels were significantly decreased by transfecting iSp1, iSp3, and iSp4 by 40, 86, and 77% respectively, demonstrating the role of Sp proteins in mediating E 2 F1 mRNA expression.…”
Section: Role Of Sp Proteins Of Hormonal Activation Of Psp1mentioning
confidence: 61%
See 1 more Smart Citation
“…The final concentration of siRNAs in each well was 140 nM. Thirty-six hours after transfection, cells were treated with DMSO, 10 nM E2, or 10 nM TCDD for 5 h, and nuclear extracts were obtained and analyzed by Western blot analysis for AhR, ER␣, and Sp1 proteins essentially as described elsewhere (1). Replicate (three) experiments were carried out to quantitate the effects of siRNA for the AhR on TCDD-induced downregulation of ER␣.…”
mentioning
confidence: 99%
“…19,20 Along this line, several recent studies have documented: (a) successful downregulation of BCR-ABL expression, resulting in increased apoptosis and decreased proliferation, in chronic myeloid leukemia cells; 21,22 (b) the MDR1 downregulation followed by chemosensitization of human pancreatic and gastric cell lines; 23 (c) combined inhibition of Bcl-2 and Raf-1 in human myeloid leukemia cells resulting in induction of apoptosis and chemosensitization. 24 Bearing in mind that RNAi is feasible in MCF-7 cell line [25][26][27] and that these cells are known to be relatively resistant to etoposide and doxorubicin, 28,29 the purpose of this study was to investigate if specific downregulation of bcl-2 or xIAP gene expression by RNAi sensitized MCF-7 cells to those chemotherapeutic drugs.…”
mentioning
confidence: 99%